Management of resources in nursing: beyond leadership - Cano-Serna, Delby Antonio; Correa Bolívar, Natalia Andrea; Flórez Rendón, Weimar Alexander; Giraldo Giraldo, Yaison Dorney; Monsalve Cuervo, Mónica Katerín; Restrepo Otálvaro, Andrés Felipe (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> This article reflects upon the reach of the contribution from nursing in the management and development of public policies for adequate assignment of resources that facilitate better healthcare in the Colombian population. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->